The Magnetohydrodynamics Casson Fluid Flow, Heat and Mass Transfer Due to the Presence of Assisting Flow and Buoyancy Ratio Parameters - Parvin, Shahanaz; Mohamed Isa, Siti Suzilliana Putri; Md. Arifin, Norihan; Md Ali, Fadzilah (CFD Letters, 2021)
The assisting boundary layer flow, heat and mass transfer have wide applications in engineering devices and in nature: for example, nuclear reactors, heat exchangers, solar receivers, atmospheric flow and lake circulation. Therefore, the numerical study of boundary layer flow, heat and mass transfer on Newtonian or non-Newtonian fluid has to be developed, as a reference to experimental works. Therefore, the mathematical modelling and numerical solutions of boundary layer flow, heat and mass transfer on magneto-hydrodynamics Casson fluid are reported in this paper. The model problem is subjected to the presence of mixed convection with assisting flow, together with the buoyant feature. The Casson fluid is assumed to flow over an exponentially stretching sheet, together with the exponential variations of fluid temperature and fluid concentration. The momentum, energy and concentration equations are formed as the controlling equations and written as partial differential equations (PDE). Subsequently, these equations were transformed into the ordinary differential equations (ODE) by using the similarity transformation. Finally, the ODE are solved numerically by bvp4c program in MATLAB software. The graphs of velocity, temperature and concentration profiles and the numerical values of skin friction coefficient, local Nusselt number and local Sherwood number are presented. These results are obtained due to the controlling parameter, namely as magnetic field, assisting flow and buoyancy ratio parameters. As a result, the increment and decrement of the velocity, temperature, concentration, skin friction coefficient, local Nusselt number and local Sherwood number are influenced by magnetic field, assisting flow and buoyancy ratio parameters.